Predicting Retention, Understanding Attrition: A Prospective Study of Foundation Year Students. (30th June 2016) - Sanders, Lalage; Daly, Annette; Fitzgerald, Katherine
The aim of this study was to evaluate two psychometric tools for identifying students at risk of failing to progress from a Foundation Year (FY) programme, a preparatory programme for those without the qualifications to enrol directly on to an undergraduate degree. Students from four FY programmes across two UK universities were invited to complete the survey at the start of the academic year (Time-1) and again towards the end of the FY (Time-2). The survey comprised the Academic Behaviour Confidence and Performance Expectation Ladder scales, designed to measure students' expectations of their academic performance and achievement. From a total of 198 participants (85% of enrolments), 90 completed measures at both points. End of year examining board outcomes were matched to the survey data. Time 1 data showed that two subscales of the confidence measure, Grades and Attendance, were indicative of subsequent progression issues. At Time 2, diminishing expectations were evident amongst those who subsequently failed to progress, indicating a process of disengagement. Therefore these measures could be used to identify students who might benefit from targeted interventions to help uncertain new entrants access the benefits that Higher Education can provide.